Central Javanese Adaptation To The Islamic Concept Of Aesthetics - Duffort, Sulaiman (2006)
In addition to politics, economics, sociology, and theology, aesthetics as the study of beauty is proposed as a legitimate approach to Islamic cultures. A qualitative research style is developed to investigate various phenomena of beauty as observed in Central Javanese culture. An analysis is attempted to discriminate aspects of Javanese life and thought that are Islamically acceptable from those that may not be.Several visits were made to Solo and Yogyakarta in Central Java, both the cities and surrounding villages. Four categories of investigation were attempted – Religion and the Unseen, The Aesthetics of Femininity, Entertainment and the Arts, and Architecture and the Environment. A questionnaire was developed and distributed to one hundred thirty informants, following the four-part categorization mentioned above. Many interviews with focused groups were conducted comprising individuals willing to discuss “halal” and “haram” aspects of the beauty of various activities of their daily lives. Javanese palace ceremonies, village cultural activities, public concerts, radio and television shows, magazines, and other media were scrutinized for both “halal” and “haram” expressions of artistic, photogenic, or musical beauty. It became evident that informants described as “beautiful” those of their religious and social experiences toward which they were subsequently most highly drawn and motivated. The approach to Javanese Islamic culture as an aesthetic entity yielded a collation of various categories of Islamic life that could not be subsumed under any other category.